Culture, Behaviour, and the 8200 cal BP Cold Event : Organisational Change and Culture Environment Dynamics in Late Mesolithic Northern Fennoscandia - Manninen, Mikael A. (Helsingin yliopisto, 2014)
This dissertation focuses on Late Mesolithic (ca. 8450 6850 cal BP) lithic technological changes in the northernmost parts of Finland, Norway, and Sweden and on the relationship between these changes and the 8.2 ka climate event that was caused by a disruption in the North Atlantic Thermohaline circulation. The study uses a framework derived from Darwinian evolutionary theory and acknowledges the effects of both environmental constraints and socially transmitted information, i.e., culture, in the way lithic technology was organised in the studied region. The study discusses whether climatic cooling and its effects on the biotic environment could explain the way lithic technology and settlement patterns were reorganised during the Late Mesolithic. The dissertation takes an organisational approach to the study of past cultural change and seeks to understand changes in prehistoric material culture by studying lithic technology and settlement configuration using lithic technological, statistical, and spatial analyses. The results suggest that Late Mesolithic coastal communities were affected by a marked decrease in marine productivity that resulted from the cooling caused by the 8.2 ka event and a subsequent cold episode at ca. 7700 cal BP. It is concluded that the technological changes that occurred during the marine cooling were a result of developments that led to increased use of terrestrial resources and an accompanying long-distance coast/inland residential mobility pattern. The study contributes to a wider field of research into past climate change as a factor in prehistoric ecological, cultural, and behavioural change and provides reference material for studies on the impacts of future climate change on human communities. The results suggest that in northernmost Fennoscandia, the marine ecosystem is particularly sensitive to disturbances in the North Atlantic oceanographic system. In addition, the study provides new knowledge concerning the relationships between raw material availability, lithic technology, ...